2021
DOI: 10.1002/hep4.1830
|View full text |Cite
|
Sign up to set email alerts
|

Low Lipoprotein(a) Levels Predict Hepatic Fibrosis in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Dyslipidemia and cardiovascular complications are comorbidities of nonalcoholic fatty liver disease (NAFLD), which ranges from simple steatosis to nonalcoholic steatohepatitis, fibrosis, and cirrhosis up to hepatocellular carcinoma. Lipoprotein(a) (Lp(a)) has been associated with cardiovascular risk and metabolic abnormalities, but its impact on the severity of liver damage in patients with NAFLD remains to be clarified. Circulating Lp(a) levels were assessed in 600 patients with biopsy-proven NAFLD. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…Inverse correlation between fatty liver disease and Lp(a) levels was reported in a large Korean study of over 22,000 participants [12]. In addition, recent studies have found that in patients with fatty liver disease, low Lp(a) levels correlate with the degree of fibrosis [61,62]. In the present analyses, we observed the highest prevalence of fatty liver in individuals with constantly low (<5 mg/dL) Lp(a) levels.…”
Section: Tablesupporting
confidence: 77%
“…Inverse correlation between fatty liver disease and Lp(a) levels was reported in a large Korean study of over 22,000 participants [12]. In addition, recent studies have found that in patients with fatty liver disease, low Lp(a) levels correlate with the degree of fibrosis [61,62]. In the present analyses, we observed the highest prevalence of fatty liver in individuals with constantly low (<5 mg/dL) Lp(a) levels.…”
Section: Tablesupporting
confidence: 77%
“…In support of the functional relevance of SAM/MAT1A in metabolic disease, MAT1A-knockout mice show NASH and dyslipidemia [ 38 ]. All four proteins are produced in the liver as products of their respective liver-expressed genes [ 34 , 37 , 39 , 40 ]. Plasma concentrations of LPA and IGFBP-1 have previously been reported to correlate with hepatic mRNA levels [ 39 , 40 ], while no association between gene expression levels of SERPINF2 and α2AP protein levels was found in hepatitis C virus-infected patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…All four proteins are produced in the liver as products of their respective liver-expressed genes [ 34 , 37 , 39 , 40 ]. Plasma concentrations of LPA and IGFBP-1 have previously been reported to correlate with hepatic mRNA levels [ 39 , 40 ], while no association between gene expression levels of SERPINF2 and α2AP protein levels was found in hepatitis C virus-infected patients [ 36 ]. To the best of our knowledge, comparative studies on plasma concentrations of SAM and hepatic expression levels of MAT1A have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the gold standard to diagnose patients with NASH is still considered to be liver biopsy, demonstrating the typical fibrosis pattern, which cannot be seen via imaging methods. Currently, although there is no readily available, reliable, and non-invasive method to identify the progression of steatosis to NASH and fibrosis, altered levels of lipoprotein (a) (Lp(a)) [ 23 ] and several biomarkers of inflammation (such as ferritin and high-sensitivity C reactive protein (CRP)) and apoptosis (cytokeratine 18 (CK-18)) [ 24 ] have been associated with the diagnosis of NASH in NAFLD patients. Moreover, the NAFLD Activity Score (NAS) is used in clinical trials for evaluating the changes in histological features caused by therapeutic interventions.…”
Section: Diagnosis Of Nafld/nashmentioning
confidence: 99%